Optimization of Transfer Quality Factor of Limited-Size Coils for Series-Series Compensated Inductive Power Transfer System - Peizhou Liu; Tiande Gao; Zhaoyong Mao (Magnetochemistry, 2022)
For an inductive power transfer system, high transfer quality factor means that the system can obtain large theoretical transmission efficiency. In this paper, a method of coil optimization in a limited space to improve the transfer quality factor for a series-series compensated inductive power transfer system is presented. High transfer quality factor in a limited space can be achieved by determining the optimal number of turns with equal turn spacing coil, and then optimizing the distance between adjacent turn. The results of finite element simulation and experimental measurement show that the method proposed in this paper can obtain a higher transfer quality factor than the conventional method of winding coil with equal turn spacing. The method proposed in this paper can be used to guide the optimal design of coils in a limited space.